2021
DOI: 10.37669/milliegitim.902519
|View full text |Cite
|
Sign up to set email alerts
|

Göçmen Öğretmen Adaylarinin Eği̇ti̇m Fakültesi̇nde Almiş Olduklari Eği̇ti̇me İli̇şki̇n Algilari

Abstract: Bu araştırmanın amacı, göçmen öğretmen adaylarının eğitim fakültesini tercih etme gerekçeleri ile eğitim fakültesinde almış oldukları eğitime ilişkin algılarını incelemektir. Nitel araştırmalardan olgubilim deseninin benimsendiği araştırmanın katılımcılarını, 2020-2021 öğretim yılında Türkiye’de bir devlet üniversitesinin eğitim fakültesinde öğrenim gören 20 göçmen öğretmen adayı oluşturmuştur. Araştırmanın verileri odak grup görüşmesiyle toplanmış ve tematik analiz tekniği ile çözümlenmiştir. Araştırma sonucu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
1
0
2
Order By: Relevance
“…Besides, Ribeiro's (2016) study also revealed a similar change in learners' perspective from an ethnocentric to an ethnorelative one. Holding a different viewpoint, Çetin and Ağçam's (2021) study pointed out the criticality of gaining such a perspective for positive classroom dynamics and revealed that immigrant undergraduate students in Türkiye experience socialization problems in the classroom stemming from their own ethnocentric attitudes and prejudices. Within the framework of interculturality in language teaching, great importance is attached to any kind of practices through which learners become aware of and identify their own ethnocentric attitudes and behaviours and through which cultural differences are dealt with through an ethnorelative lens (Baker, 2012;Byram, 2021).…”
Section: Understanding Selfmentioning
confidence: 99%
“…Besides, Ribeiro's (2016) study also revealed a similar change in learners' perspective from an ethnocentric to an ethnorelative one. Holding a different viewpoint, Çetin and Ağçam's (2021) study pointed out the criticality of gaining such a perspective for positive classroom dynamics and revealed that immigrant undergraduate students in Türkiye experience socialization problems in the classroom stemming from their own ethnocentric attitudes and prejudices. Within the framework of interculturality in language teaching, great importance is attached to any kind of practices through which learners become aware of and identify their own ethnocentric attitudes and behaviours and through which cultural differences are dealt with through an ethnorelative lens (Baker, 2012;Byram, 2021).…”
Section: Understanding Selfmentioning
confidence: 99%
“…Öğrencilerin eğitimi sürecindeki durumları üzerine yapılan çalışmalarda eğitim sürecinde karşılaşılan sorunlar, programın değerlendirilmesi, öğrenci ve öğretmen algıları ve toplumsal uyumlarına yönelik farklı çalışmalar (Alshirah, 2019;Akdemir, 2020;Uzunay, 2022;Ardoğan, 2021;Şahin, 2019;Uygun, 2020;Pelin, 2021) yapılmıştır. Özellikle sığınmacıların topluma uyumunu sağlayacak çalışmalar farklı disiplinlerin perspektifleri ile (Aydeniz ve Sarıkaya, 2021;Bahadır, 2021;Çetin ve Ağçam, 2021;Demircan, 2019;Halavurt ve Zeteroğlu, 2018;Işık ve Bahat, 2021;Selimbeyoğlu, 2022;Sertkaya ve Yılmaz, 2016;Turan ve Fansa, 2021;Ünal ve Gedik, 2022;Yurdakul ve Tok, 2018) araştırılmıştır. Ancak ilgili alan yazın incelendiğinde Sosyal Bilgiler dersinin sığınmacıların topluma entegrasyonu ile ilgili çalışmaların oldukça sınırlı ve yeterli olmadığı görülmektedir.…”
Section: Introductionunclassified
“…Göç ile ilgili daha önce yapılan araştırmalara bakıldığında göçmen ve mülteci hareketlerine yönelik olarak (Aksoy, 2012;Erdil, 2020;Ergüven & Özturanlı, 2013;Fansa, 2021;Kara & Korkut, 2010;Kartal & Başçı, 2014;Kurt, 2006;Samur, 2008;Yıldız, 2013); göçün eğitime etkisine yönelik olarak (Aksoy, 2020;Avcı vd., 2013;Aydeniz & Sarıkaya, 2021;Çetin & Ağçam, 2021;Çolak & İşeri, 2022;Demircan, 2019;Dilek & Demirel, 2021;Ereş, 2015;Karaman & Bulut, 2018;Sakız, 2016;Selçuk vd., 2021;Yurdakul & Tok, 2018;Uysal, 2022); göçün sosyal yaşama etkisine yönelik olarak (Aker vd., 2002;Altuntepe & Öztürk, 2008;Ekici & Tuncel, 2015;Özkan, 2019;Selimbeyoğlu, 2022;Sözer, 2019;Tümtaş & Ergun, 2016;Yavuz, 2013;Yardım, 2017); göçün ekonomiye etkisine yönelik olarak (Altunç vd., 2017;Görgün, 2018;Göv & Dürrü, 2017;Konuk & Engin, 2023); göçün aile ve çocuklar üzerindeki etkisine yönelik olarak (Baş vd., 2017;Çağlak, 2017;Engin, 2021;Gülmez & Öztürk, 2018;Halavurt & Şahin Zeteroğlu, 2018;…”
unclassified